Effect of Alteration in Precipitation Amount on Soil Microbial Community in a Semi-Arid Grassland - Li, Junyong; Benti, Girmaye; Wang, Dong; Yang, Zhongling; Xiao, Rui (Frontiers in Microbiology, 2022)
Climate models predict significant changes in precipitation magnitude in semi-arid grasslands, so it is vital to improve our understanding of how changing precipitation affects microbial communities in grassland ecosystems. Using a long-term field manipulation experiment, we evaluated the responses of microbial communities to a decrease (DP) and an increase (IP) in precipitation on a semi-arid grassland in northern China. The results showed that bacterial species richness decreased significantly with DP but remained stable under IP. Relative abundance of oligotrophic, slow-growing bacterial phyla (e.g., Chloroflexi and Acidobacteria) increased with DP but decreased with IP, whereas the relative abundance of copiotrophic, fast-growing bacterial phyla (e.g., Proteobacteria and Bacteroidetes) decreased with DP but increased with IP. In contrast, diversity, species composition, and relative abundance of different fungal phyla change little with DP or IP. These results indicate a greater sensitivity of bacteria to precipitation changes than fungi, and the sensitivity of bacteria to DP was higher than IP. Our findings are important for understanding soil microbial dynamics under future climate change scenarios.